Advertising for Europe. TV ads during the 2009 European election campaign in four countries - Holtz-Bacha, Christina; Johansson, Bengt; Leidenberger, Jacob; Maarek, Philippe; Merkle, Susanne (Nordicom Review, 2012)
This study analyzes and compares party ads that were broadcast on television during the 2009 European Election campaign in France, Germany, Sweden and the UK. Even though electoral TV ads have never reached the same importance in European countries as in the US, such ads are to be regarded as an expression of the specific political culture of a country and therefore have relevance beyond election campaigns. An international comparison of ads produced for the same event is particularly suited to revealing similarities across cultures as well as national idiosyncrasies. Additionally, the present study demonstrates a methodological approach that defines a 'sequence' as the unit of analysis instead of the whole spot, and thus it is different from previous research on electoral advertising.
WiSo-Import:2015-03-26:4165
Keywords: electoral advertising; European election; content analysis; international com-parison